2016
DOI: 10.1016/j.nutres.2015.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Dietary Inflammatory Index scores are associated with healthier scores on other dietary indices

Abstract: Dietary components are important determinants of systemic inflammation; a risk factor for most chronic diseases. The Dietary Inflammatory Index (DII) was developed to assess dietary inflammatory potential. It was hypothesized that anti-inflammatory DII scores would be associated with ‘healthier’ scores on other dietary indices. The Energy Balance Study is an observational study focusing on energy intake and expenditure in young adults; only baseline data were used for this analysis (n=430). The DII, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
119
3
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 135 publications
(142 citation statements)
references
References 29 publications
12
119
3
8
Order By: Relevance
“…With regards to the relation between DII and gender [45] showed higher score in females than males, this was partially due to the fact that males had higher absolute intake amounts of many anti-inflammatory components of the DII this supported the results in the present study in which females had slightly higher DII score than male, but those results did not achieve statistical significance. In contrast with our finding a study showed controversial results in which the DII score was higher in male [46]. The differences among gender were due to underreporting, in which men gave more details about there diet and more accurate portion size than women during the interview.…”
Section: Discussioncontrasting
confidence: 99%
“…With regards to the relation between DII and gender [45] showed higher score in females than males, this was partially due to the fact that males had higher absolute intake amounts of many anti-inflammatory components of the DII this supported the results in the present study in which females had slightly higher DII score than male, but those results did not achieve statistical significance. In contrast with our finding a study showed controversial results in which the DII score was higher in male [46]. The differences among gender were due to underreporting, in which men gave more details about there diet and more accurate portion size than women during the interview.…”
Section: Discussioncontrasting
confidence: 99%
“…Specific nutrients also are considered to be anti‐inflammatory, such as fibre, folate and vitamins E and C . Our results are consistent with these findings; in addition, we also report an inverse association between parental E‐DII and HEI scores observed in previous studies …”
Section: Discussionsupporting
confidence: 93%
“…Specific nutrients also are considered to be anti-inflammatory, such as fibre, folate and vitamins E and C. 40 Our results are consistent with these findings; in addition, we also report an inverse association between parental E-DII and HEI scores observed in previous studies. 41 Limited data regarding maternal DII or its potential influence on offspring birth outcomes or childhood health exist. In our study, stress may underlie these findings.…”
Section: E-dii Scoresmentioning
confidence: 99%
“…Variable selection began as a series of bivariate analyses (ie, exposure + potential covariate) where covariates with a P≤.20 were added to a "full" model. [25][26][27] The covariates that were entered into the first model (full model) were age, BMI, intervention group, distance to data collection site, partner status, depression symptoms, and employment status. Backward elimination procedures were used to develop "final" models that included all covariates that were statistically significant (P<.05) The Likelihood Ratio Test (LRT) was also performed to assess the difference between models as variables were removed.…”
Section: Discussionmentioning
confidence: 99%